Machine Learning Techniques On Brain Image Biomarkers - Reddy, B.Vamsi Vardhan; vidyullatha P,; Gowtham Y,; RajGopal, G.Dinesh; Babu.P, Haran (International Journal of Psychosocial Rehabilitation, 2020)
Classifiers of machine learning algorithms have been successfully applied in recent years to predict cancer based on multistage image segmentation and gene expression data. Many classification algorithms have been used and developed in recent years to determine the presence of tumors and to determine the rate of development .The fundamental target of the venture is to examine the performances between these multiple algorithms of Machine learning Techniques. Among them, the SVM shows high precision compared to many other classifiers.